Penal Mediation as the Concept of Restorative Justice in the Draft Criminal Procedure Code - Adi, Emmanuel Ariananto Waluyo (Universitas Negeri Semarang, 2021)
The law recognizes both litigation and non-litigation settlement mechanisms, but it is almost not explicitly regulated for non-litigation settlement in criminal cases. Non-litigation in criminal recognizes the concept of restorative justice for the public interest, which is different from the private realm in civil. The concept of restorative justice exists to rehabilitate the state of criminals so that they are accepted back into the community. The concept of restorative justice is manifested in the mediation mechanism in criminal law in the form of penal mediation, but penal mediation does not yet have a legal umbrella. The non-progressive normative application of the law results in the overcapacity of prisons/remand centres. Currently, the Draft Criminal Procedure Code (hereinafter as RKUHAP) is being drafted, which does not yet regulate the application of non-litigation solutions. Later, it can be applied by law enforcement agencies so that problems such as overcapacity prisons are resolved and the creation of peaceful order in the community. This study aims to provide a view of the concept of penal mediation in criminal procedural law to serve as an aspiration for the consideration of the parties involved in the preparation of the substance of the RKUHAP. This paper uses a normative approach with technical analysis using hermeneutic analysis and interpretation methods.